Conservative surgery of the oviduct - Rearden, Moisés (Cirugía del Uruguay, 1973)
Conservative surgery at the oviductllevel is dealt with. Yt is included a statistic on 200 personal cases as well as an original technic: "tunelization uterus-ovary" tu supply the. lack of oviduct. Yt is included a dispter on conservative surgery on operations due to a ectopic pregnancy, suggesting the 30 possíbility of makíng, not only a plastic surgery on the oviduct affected by the process, but also the treatment of the ovíduct that is supposed to be normale, when a precise índícation emerges from the intra-operation study. The strict norms that must guide this type of surgery on their indications as well as in their execution.